Syamsul Anwar’s Vision: Establishing a Unified Global Islamic Calendar - Arafat, Muhammad; Budiwati, Anisah (Universitas Islam Negeri Mataram, 2025)
This article examines Syamsul Anwar's endeavours to promote the unification of the global Hijri calendar, which is essential for aligning Islamic religious observances, including Ramadan, Eid al-Fitr, and Eid al-Adha. Discrepancies in establishing the commencement of the Hijri month, especially in Indonesia, arise from the contrasting methodologies employed by Nahdatul Ulama, which relies on rukyat (moon sighting), and Muhammadiyah, which utilizes hisab (astronomical calculations). Syamsul Anwar's methods aims to amalgamate these techniques via five fundamental principles: acknowledgement of hisab, transference of imkanu rukyat, the cohesion of matlak, worldwide synchronization of days and dates, and acknowledgement of the International Date Line. The study employs qualitative methodologies, such as observation, interviews, and document analysis, to comprehend Anwar's perspectives. Notwithstanding extensive backing from Islamic astronomy professors, obstacles persist in Indonesia owing to the cultural importance of rukyat. This study suggests that additional research and discourse are necessary to reconcile these disparities and establish a worldwide unified Hijri calendar, thereby minimizing inconsistencies in religious rituals throughout the Muslim world.